Pooled Open Blocks Shorten Wait Times for Nonelective Surgical Cases. Issue 1 (July 2015) - Zenteno, Ana C.; Carnes, Tim; Levi, Retsef; Daily, Bethany J.; Price, Devon; Moss, Susan C.; Dunn, Peter F.
Abstract : Objective: Assess the impact of the implementation of a data-driven scheduling strategy that aimed to improve the access to care of nonelective surgical patients at Massachusetts General Hospital (MGH). Background: Between July 2009 and June 2010, MGH experienced increasing throughput challenges in its perioperative environment: approximately 30% of the nonelective patients were waiting more than the prescribed amount of time to get to surgery, hampering access to care and aggravating the lack of inpatient beds. Methods: This work describes the design and implementation of an "open block" strategy: operating room (OR) blocks were reserved for nonelective patients during regular working hours (prime time) and their management centralized. Discrete event simulation showed that 5 rooms would decrease the percentage of delayed patients from 30% to 2%, assuming that OR availability was the only reason for preoperative delay. Results: Implementation began in January 2012. We compare metrics for June through December of 2012 against the same months of 2011. The average preoperative wait time of all nonelective surgical patients decreased by 25.5% ( P < 0.001), even with a volume increase of 9%. The number of bed-days occupied by nonurgent patients before surgery declined by 13.3% whereas the volume increased by 4.5%. Conclusions: The large-scale application of an open-block strategy significantly improved the flow of nonelective patients at MGH when OR availability was a major reason for delay. Rigorous metrics were developed to evaluate its performance. Strong managerial leadership was crucial to enact the new practices and turn them into organizational change. Abstract : Supplemental Digital Content is Available in the Text.We describe the design and implementation of a data-driven scheduling strategy that reserves and centralizes the administration of operating room capacity, exclusively for nonelective patients. The goal was to give these patients timelier access to surgery, while maintaining an efficient use of the available resources.